Trailing TRAIL Resistance: Novel Targets for TRAIL Sensitization in Cancer Cells - Trivedi, Rachana; Mishra, Durga Prasad (Frontiers in Oncology, 2015)
Resistance to chemotherapeutic drugs is the major hindrance in the successful cancer therapy. The tumor necrosis factor- related apoptosis- inducing ligand (TRAIL) is a member of the Tumor Necrosis Factor (TNF) family of ligands which initiates apoptosis in cancer cells through interaction with the death receptors DR4 and DR5. TRAIL is perceived as an attractive chemotherapeutic agent as it specifically targets cancer cells while sparing the normal cells. However TRAIL therapy has a major limitation as a large number of the cancer develop resistance towards TRAIL and escape from the destruction by the immune system. Therefore, elucidation of the molecular targets and signaling pathways responsible for TRAIL resistance is imperative for devising effective therapeutic strategies for TRAIL resistant cancers. Although, various molecular targets leading to TRAIL resistance are well studied, recent studies have implicated that the contribution of some key cellular processes towards TRAIL resistance need to be fully elucidated. These processes primarily include aberrant protein synthesis, protein misfolding, ubiquitin regulated death receptor expression, metabolic pathways, epigenetic deregulation and metastasis. Novel synthetic/natural compounds that could inhibit these defective cellular processes may restore the TRAIL sensitivity and combination therapies with such compounds may resensitize TRAIL resistant cancer cells towards TRAIL-induced apoptosis. In this review, we have summarized the key cellular processes associated with TRAIL resistance and their status as therapeutic targets for novel TRAIL-sensitizing agents.